Catalytic enantioselective intermolecular cycloadditions of 2-diazo-3,6-diketoester-derived carbonyl ylides with alkene dipolarophiles. - Hodgson, D; Brückl, T; Glen, R; Labande, A; Selden, D; Dossetter, A; Redgrave, A (2004)
Catalyzed cascade reactions that generate molecular complexity rapidly and in an enantioselective manner are attractive methods for asymmetric synthesis. In the present article, chiral rhodium catalysts are shown to effect such a transformation by using a range of 2-diazo-3,6-diketoesters with bicyclo[2.2.1]alkenes and styrenes as reaction partners. The reactions are likely to proceed by formation of a catalyst-complexed carbonyl ylide from the diazo compound, followed by intermolecular cycloaddition with the alkene dipolarophile. It was possible to obtain high levels of asymmetric induction [up to 89% enantiomeric excess (ee) and 92% ee for the two chiral catalysts investigated]. Enantioselectivity is not highly sensitive to substituent variation at the ketone that forms the ylide; however, branching does improve ee. Observations of dipolarophile-dependent enantiofacial selectivity in the cycloadditions indicate that the dipolarophile can be intimately involved in the enantiodiscrimination process.